Clinical impact and a prognostic marker of early rituximab treatment after rituximab reimbursement in Korean pemphigus patients - Song, Ahreum; Jang, Jieun; Lee, Ayeong; Min, Seo Yeon; Lee, Sang Gyun; Kim, Soo-Chan; Shin, Jaeyong; Kim, Jong Hoon (Frontiers in Immunology, 2022)
Pemphigus is an autoimmune mucocutaneous blistering disease caused by autoantibodies to desmogleins. Rituximab effectively treats pemphigus by inducing remission and rapidly reducing corticosteroid dosages. In Korea, the high cost of rituximab had been a burden until the National Health Insurance started to cover 90% of rituximab cost via reimbursement for severe pemphigus patients. We analyzed 214 patients with pemphigus treated with their first round of rituximab. Time to initiating rituximab and time to partial remission under minimal therapy (PRMT) were both significantly shorter after the rituximab reimbursement policy. Total steroid intake to PRMT and complete remission (CR) were less in patients who were diagnosed after the reimbursement. The interrupted time series (ITS) model, a novel analysis method to evaluate the effects of an intervention, showed a decrease in total systemic corticosteroid intake until PRMT after reimbursement began. In peripheral blood mononuclear cells from patients with pemphigus vulgaris, the relative frequencies of desmoglein 3-specific CD11c+CD27‒IgD– atypical memory B cells positively correlated with the periods from disease onset to rituximab treatment and to PRMT as well as the total systemic corticosteroid intake until PRMT. We found that early rituximab therapy, induced by the reimbursement policy, shortened the disease course and reduced the total corticosteroid use by pemphigus patients. The decreased frequency of circulating desmoglein-specific atypical memory B cells can be used as a surrogate marker for a good prognosis after rituximab.